Transforming Outpatient Registration: A Quality Management Approach For Community Service At RSAU Dr. M.Munir - Retno Dewi Prisusanti; Enggal Pratama Gumilang (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Patient registration services are a crucial component in providing a positive experience for patients in healthcare facilities.This study aims to transform the outpatient registration services at RSAU Dr. M. Munir through a quality management approach, focusing on improving efficiency, data accuracy, and patient satisfaction. The methods used include initial observation, interviews, SWOT analysis, and the implementation of a pilot project involving an online registration system and staff training. The study results show that the interventions successfully reduced registration time from an average of 15 minutes to 8 minutes, improved patient data accuracy by 30%, and increased patient satisfaction levels from 65% to 85%. The evaluation also highlights the importance of regular staff training and community involvement in ensuring the success and sustainability of the changes implemented. The conclusion of this study is that effective quality management implementation can transform patient registration services into a more efficient and patient-friendly process. The recommendations include expanding the implementation of the online registration system, developing regular training programs, and enhancing supporting facilities to strengthen the patient experience. These findings are expected to contribute significantly to the development of healthcare services that focus on quality and patient satisfaction at RSAU Dr. M. Munir and other healthcare facilities.